Pratiques harmonisées d'accompagnement des étudiants et impact sur leur sentiment de sécurité - Patricia Rached
In this paper, we examine the impact of a students' academic advisory program, based on harmonized practices between advisors, on students' feeling of security and motivation to learn. We also look at the extent to which the concept of advisory can be considered as an institutional culture in the context of the University of Saint-Joseph in Beirut. Quantitative and qualitative data were collected from five campuses through a questionnaire completed by 1530 students and focus groups composed of advisors and students. Results showed a positive link between the concepts of "harmonized practices" and students' "feeling of security" that led to students' motivation for learning. This study also helped in drawing guidelines for a formal academic advising program applicable not only at the University of Saint-Joseph but also in other higher education institutions.